Surface-Coated Polylactide Fiber Meshes as Tissue Engineering Matrices with Enhanced Cell Integration Properties. (15th June 2014) - Schnabelrauch, Matthias; Wyrwa, Ralf; Rebl, Henrike; Bergemann, Claudia; Finke, Birgit; Schlosser, Michael; Walschus, Uwe; Lucke, Silke; Weltmann, Klaus-Dieter; Nebe, J. Barbara
Abstract : Poly(L-lactide- co -D/L-lactide)-based fiber meshes resembling structural features of the native extracellular matrix have been prepared by electrospinning. Subsequent coating of the electrospun fibers with an ultrathin plasma-polymerized allylamine (PPAAm) layer after appropriate preactivation with continuous O2 /Ar plasma changed the hydrophobic nature of the polylactide surface into a hydrophilic polymer network and provided positively charged amino groups on the fiber surface able to interact with negatively charged pericellular matrix components. In vitro cell experiments using different human cell types (epithelial origin: gingiva and uroepithelium; bone cells: osteoblasts) revealed that the PPAAm-activated surfaces promoted the occupancy of the meshes by cells accompanied by improved initial cell spreading. This nanolayer is stable in its cell adhesive characteristics also after γ -sterilization. An in vivo study in a rat intramuscular implantation model demonstrated that the local inflammatory tissue response did not differ between PPAAm-coated and untreated polylactide meshes.